2021
DOI: 10.1108/ics-06-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

Improving data quality for human-as-a-security-sensor. A process driven quality improvement approach for user-provided incident information

Abstract: Purpose In the past, people were usually seen as the weakest link in the IT security chain. However, this view has changed in recent years and people are no longer seen only as a problem, but also as part of the solution. In research, this change is reflected in the fact that people are enabled to report security incidents that they have detected. During this reporting process, however, it is important to ensure that the reports are submitted with the highest possible data quality. This paper aims to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…For example, if an employee notices a security incident, they need to be able to contribute their observations to the Data Collection phase of the Incident Detection Lifecycle. Initial approaches to this already exist in the form of the human-as-a-security-sensor paradigm [32,33]. However, further research is needed in this direction to solve this problem in an applicable way.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…For example, if an employee notices a security incident, they need to be able to contribute their observations to the Data Collection phase of the Incident Detection Lifecycle. Initial approaches to this already exist in the form of the human-as-a-security-sensor paradigm [32,33]. However, further research is needed in this direction to solve this problem in an applicable way.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Analyzing and steering Data Quality in analytical processes are very relevant activities in computer science and data analysis [e.g., Ahmed et al (2018) for improvement of data quality in intelligent e-CRM applications, or Vielberth et al (2021) for security incidents], where many automatic tools exist that support these tasks, be it to different degrees. Recent work by Ehrlinger et al (2019) surveyed 667 software tools dedicated to data quality.…”
Section: Related Workmentioning
confidence: 99%
“…The study confirmed that showing data quality measures and allowing the user to consider them during data exploration produces different behavior than not doing it, and it is mentioned as further motivation for our proposal. Vielberth et al (2021) propose a process-driven quality improvement approach for human-as-a-security-sensor information. However, differently from our approach, the authors just provide the process and a use case based on tabular data, without providing any means, visual or not, to support the user in this process.…”
Section: Related Workmentioning
confidence: 99%